APPLYING STATISTICAL ANALYSIS TO DETERMINE NUMBER OF COFFEE SHOPS - N. Cheremisina; T. Cheremisina; M. Serdyukova (Вестник Северо-Кавказского федерального университета)
The consumer market of goods and services is one of the main and important components of the structure of the modern economy. It is here that the daily needs of the population are realized, the level of satisfaction of which, in the final analysis, determines the efficiency of the economy as a whole. This article provides a historical overview of the evolution of the sphere of public catering in Russia; on the basis of official statistics, the development of Russian catering in recent years is analyzed. The analysis of the obtained data was carried out using such statistical methods as nonparametric analysis based on multiple rank correlation coeicient, multiple correlation and regression analysis; using statistical analysis methods, the factors influencing the development of catering, and in particular coffee shops, in Russian cities with a population of more than a million people were identiied.